Contesting authentic practice and ethical authority in adventure tourism - Rickly, J.M.; Vidon, Elizabeth S. (Taylor & Francis, 2017)
This paper examines the discourses of authenticity and ethics used among adventure tourists regarding the use of the natural environment. In one case, full-time traveling rock climbers use their dedication to the sport and annual visits to the Red River Gorge as evidence for their authoritative voice on ethical climbing practice. While they identify the growing numbers of leisure climbers as a problem for sustainability, many also take up temporary employment as guides and are directly involved in the introduction of new climbers to the area. In another case, two groups of wilderness enthusiasts – “ADK 46ers” and “Summit Stewards” – lament the environmental and social impacts of other recreational users in the Adirondack Park. Despite being visitors themselves, Summit Stewards and 46ers use their sense of place and knowledge of Adirondack history and ecology to substantiate their authority as purveyors of ethical practice. In both cases, senses of responsibility are inspired by senses of place, but are articulated through notions of authenticity and used as justification for ethical authority. While validating their presence in these outdoor spaces, the use of such rhetoric also minimizes their own impacts yielding further tensions among user groups.